Evaluation of Chronic Constipation in Children With Autism Spectrum Disorder. Issue 2 (23rd November 2022) - Coe, Alexander; Ciricillo, Jacob; Mansi, Sherief; El-Chammas, Khalil; Santucci, Neha; Bali, Neetu; Lu, Peter L.; Damrongmanee, Alisara; Fei, Lin; Liu, Chunyan; Kaul, Ajay; Williams, Kent C.
Abstract : Objectives: Chronic constipation occurs frequently in children with autism spectrum disorder (ASD). The primary objective was to determine whether chronic constipation is associated with a higher rate of abnormal colonic motor activity in ASD children than in non-ASD children. A secondary goal was to determine if clinical variables could identify children with ASD at risk for possessing abnormal colonic motility. Methods: A retrospective, propensity-matched, case-control study compared colonic manometry (CM) of an ASD cohort and non-ASD controls with chronic constipation. Clinical variables were evaluated as potential predictors for abnormal colonic motility. Results: Fifty-six patients with ASD and 123 controls without the diagnosis of ASD who underwent CM were included. Propensity score resulted in 35 matched cohorts of ASD and controls. The rate of abnormal CM findings between ASD and matched controls (24% vs 20%, P = 0.78) did not differ significantly. A prediction model of abnormal CM that included ASD diagnosis, duration of constipation, and soiling achieved a sensitivity of 0.94 and specificity of 0.65. The risk for abnormal colonic motility increased 11% for every 1-year increase in duration of constipation. Odds for abnormal motility were 30 times higher in ASD children with soiling than controls with soiling ( P < 0.0001). Conclusions: Chronic constipation does not appear to be associated with a higher rate of abnormal colonic motility in children with ASD. Clinical information of disease duration and presence of soiling due to constipation show promise in identifying patients with ASD at a greater risk for abnormal colonic motility.